2016
DOI: 10.1016/j.ebiom.2016.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Treponema DNA from Necrophagous Flies in a Natural Ecosystem

Abstract: BackgroundRecently, the World Health Organization launched a campaign to eradicate the tropical disease yaws, caused by the bacterium Treponema pallidum subsp. pertenue; however, for decades researchers have questioned whether flies act as a vector for the pathogen that could facilitate transmission.MethodsA total of 207 fly specimens were trapped in areas of Africa in which T. pallidum-induced skin ulcerations are common in wild baboons; 88 flies from Tarangire National Park and 119 from Lake Manyara National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Vertebrate faecal metabolites (urobilinoids) detected in adult blow fly guts represent a potential means to identify when mammalian DNA originated from contact with faeces, which might help future research differentiate the source of mammalian DNA found in flies (Owings, Skaggs, Sheriff, Manicke, & Picard, 2018). Despite the potential rarity of carcass DNA in flies, our results certainly lend further support for such an approach for monitoring bacterial pathogens (Hoffmann et al, 2017;Knauf et al, 2016). Guenno et al, 1995).…”
Section: 030mentioning
confidence: 64%
See 1 more Smart Citation
“…Vertebrate faecal metabolites (urobilinoids) detected in adult blow fly guts represent a potential means to identify when mammalian DNA originated from contact with faeces, which might help future research differentiate the source of mammalian DNA found in flies (Owings, Skaggs, Sheriff, Manicke, & Picard, 2018). Despite the potential rarity of carcass DNA in flies, our results certainly lend further support for such an approach for monitoring bacterial pathogens (Hoffmann et al, 2017;Knauf et al, 2016). Guenno et al, 1995).…”
Section: 030mentioning
confidence: 64%
“…Flies have long been hypothesized to play a role in the epidemiology of yaws, with studies showing that flies can carry treponemes from lesions (Kumm, 1935;Satchell & Harrison, 1953) and, in experimental conditions, that flies transmitted the parasite from one host to another when feeding on lesions (Kumm & Turner, 1936). Furthermore, a high proportion of flies captured in two national parks in Tanzania, where wild olive baboons (Papio anubis) are infected with TPE, were found to contain T. pallidum DNA (Knauf et al, 2016); based on the low variability of the genomic regions of T. pallidum examined in their study, it was not possible to definitively determine which subspecies of T. pallidum was present in these flies, although the authors argue their results suggest that flies often come into contact with the spirochete on these baboons as there is no evidence for other T. pallidum subspecies circulating in this ecosystem (Knauf et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A possible important alternate route of infection has been discussed through the involvement of flies as a vector ( 27 , 28 ). Although both options are at least theoretically possible for NHPs ( 13 ), direct contact should be considered the most likely way of intraspecies and interspecies transmission. Such transmission is further supported by reports of the close association and interaction (play, fight, or hunt) among different NHP species ( 29 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…We added an additional washing step using 300 μL AW1 buffer and eluted the DNA twice with 100 μL AE buffer. We further purified extracted DNA using glycogen precipitation according to the protocol published in Knauf et al ( 13 ). …”
Section: Methodsmentioning
confidence: 99%
“…Pet monkeys may also function as a Treponema-reservoir for humans (32). Furthermore, it has been suggested that treponemes may be transmitted by flies (33)(34)(35)(36). In this context it may seem surprising that Tanzania, where NHPs are infected with potentially zoonotic TPE strains (13), has not reported human yaws for decades.…”
Section: Resultsmentioning
confidence: 99%